DEVELOPMENT OF FINANCIAL AND CREDIT MECHANISMS OF STATE AND PRIVATE PARTNERSHIP IN UZBEKISTAN - Olimjonova Nigora Alisherovna (Scholar Express Journals, 2023)
In this article, it is written about the development of financial and credit mechanisms in Uzbekistan regarding public and private partnership. The public-private partnership development agency under the Ministry of Finance was appointed to be responsible for the implementation of the unified state policy in the field of public-private partnership in Uzbekistan.
Keywords: Uzbekistan; financial credit; cooperation; power